2017
DOI: 10.1089/chi.2016.0126
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Perfluoroalkyl Substances and Body Fatness in Girls

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 42 publications
1
39
1
Order By: Relevance
“…Studies of PFAS also report mixed results. Our observations are congruent with two studies indicating higher exposure may result in smaller size (7, 15), while others were of larger size (10, 12, 13), null (8, 11, 14, 16), or of inverted U-shaped direction (9). The Danish National Birth Cohort first identified that PFOS and PFOA may be associated with smaller infant size, particularly in boys from 0–12 months with a subsequent analysis at 7 years showing no differences in size, albeit the direction of association remains toward lower BMI (7, 8).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Studies of PFAS also report mixed results. Our observations are congruent with two studies indicating higher exposure may result in smaller size (7, 15), while others were of larger size (10, 12, 13), null (8, 11, 14, 16), or of inverted U-shaped direction (9). The Danish National Birth Cohort first identified that PFOS and PFOA may be associated with smaller infant size, particularly in boys from 0–12 months with a subsequent analysis at 7 years showing no differences in size, albeit the direction of association remains toward lower BMI (7, 8).…”
Section: Discussionsupporting
confidence: 91%
“…Hence, cross-sectional data from the NHANES Survey 2003–2004 showed that almost all pregnant women in the U.S. had quantifiable levels of these EDCs (5), raising concerns over their long-term impact on early childhood growth. The evidence of associations between prenatal exposures to PFASs and offspring obesity from ten prospective investigations has also been equivocal (7, 8, 9, 10, 11, 12, 13, 14, 15, 16). Four studies included over 1000 participants (7, 12, 14, 16).…”
Section: Introductionmentioning
confidence: 99%
“…But most of human studies have been cross-sectional in design, and reports from longitudinal studies involved with prenatal maternal exposure are limited (Heindel et al 2015;Ranciere et al 2015). In the case of perfluoroalkyl substances (PFAS) exposure, recent studies strongly support that prenatal maternal exposure is associated with excess adiposity and obesity in childhood (Braun 2017;Braun et al 2016;Hartman et al 2017;Mora et al 2017). For example, studies from the USA found that higher prenatal perfluoroalkyl substances (PFAS) exposure was associated with a rapid increase in BMI of children between 2-8 years (Braun et al 2016), and small increases in adiposity measurements in midchildhood girls (Mora et al 2017).…”
Section: Environmental Obesogensmentioning
confidence: 99%
“…Prenatal exposures to other environmental chemicals that are possibly associated with childhood obesity include dichlorodiphenyldichloroethylene (DDE) (Tang-Peronard et al Vafeiadi et al 2015;Valvi et al 2014), hexachlorobenzene (HCB) (Vafeiadi et al 2015;Valvi et al 2014), polycyclic aromatic hydrocarbon (PAH) (Rundle et al 2012), and polybrominated diphenylethers (PBDE) (Braun et al 2016;Erkin-Cakmak et al 2015;Hartman et al 2017;Tang-Peronard et al 2014). A pooled analysis of seven European birth cohorts found that dichlorodiphenyldichloroethylene (DDE) was associated with a significant increase in weight-for-age z-score in infants (Iszatt et al 2015).…”
Section: Environmental Obesogensmentioning
confidence: 99%
“…Prenatal PFAS exposure, namely PFOS, was associated with smaller size at birth (weight, crown to heel length, and head circumference) [50,51], but larger size at 20 months (for PFOS) [50]. Additionally, prenatal exposure to PFOA and PFOS was associated with girls' percent total body fat at age nine within some strata of maternal education status [52]. While the previous studies have focused on prenatal exposure to PFAS and observed subtle disruptions to endocrine signaling and altered adipocyte profiles, the present study does not show the same effect with GWG among mothers.…”
Section: Discussionmentioning
confidence: 92%